Adolescents' peer contacts promote life satisfaction in young adulthood — A connection mediated by the subjective experience of not being lonely. (1st December 2020) - Kekkonen, Virve; Tolmunen, Tommi; Kraav, Siiri-Liisi; Hintikka, Jukka; Kivimäki, Petri; Kaarre, Outi; Laukkanen, Eila
Abstract: Life satisfaction is known to be associated with several social and mental adversities. We examined whether social activities and relationships in adolescence are related to life satisfaction in young adulthood. The psychosocial background characteristics of the study subjects (n = 787, aged 13–18 years) were recorded by using self-rated questionnaires. Five years later, the Life Satisfaction (LS) scale was used to measure the participants' life satisfaction. Of the baseline variables, a low frequency of meeting with friends and subjective loneliness among males and a low number of recreational sporting hobbies among females associated with lower life satisfaction in young adulthood. The association between the frequency of meeting friends in adolescence and life satisfaction in young adulthood was mediated by the level of loneliness and Beck Depression Inventory (BDI) score in adolescence. We conclude that loneliness in adolescence may associate with low life satisfaction and related problems in young adulthood. Investing in support and social gatherings in the adolescent community may prevent youth loneliness. Highlights: The Youth Well-being Study followed 787 adolescent students for five years. Fewer social activities associated with low life satisfaction in young adulthood. Loneliness mediated the interaction between meeting friends and life satisfaction. Youth social isolation might have longitudinal effects on individual well-being.